Prevalence and prognostic value of D‐dimer elevation in patients with AL amyloidosis. Issue 10 (2nd August 2019) - Pudusseri, Anita; Sanchorawala, Vaishali; Sloan, J. Mark; Bever, Katherine M.; Doros, Gheorghe; Kataria, Shivangi; Sarosiek, Shayna
Abstract: Light chain (AL) amyloidosis is a protein folding disorder that can affect many different organ systems, in addition to the coagulation pathway. D‐dimer, a measurement of fibrin degradation, is commonly elevated in hematologic malignancies, but the prevalence and significance of D‐dimer elevation in AL amyloidosis is unknown. We conducted an analysis of 921 patients with AL amyloidosis that presented to the Boston University Amyloidosis Center. Baseline characteristics and laboratory data of the 897 patients included in the final cohort were analyzed. Four hundred twenty three patients (47%) had an elevated D‐dimer (>0.5 μg/mL). Multivariate analysis demonstrated that a normal D‐dimer level of ≤0.5 μg/mL, and a level of >0.5 μg/mL but <1 μg/mL, conferred a lower risk of mortality (HR 0.49 and 0.59, respectively) when compared to a D‐dimer level ≥ 1 μg/mL. The increased risk of mortality in patients with a D‐dimer level ≥ 1 μg/mL was present in all cardiac stages. The median overall survival based on D‐dimer range of ≤0.5, >0.5 but <1, and ≥ 1 μg/mL was 5.86, 4.04, and 2.08 years, respectively ( P  < .001). This retrospective analysis demonstrates the high prevalence of D‐dimer elevation in AL amyloidosis and confirms that this laboratory finding is independently associated with decreased survival.